Manual therapy in the treatment of facial wrinkles and sagging: a quantitative-qualitative randomized clinical trial - Garcia, Aline de Souza Massulo; Silva, Dilane Braga da; Gonçalves, Vanessa Daniele Ferreira; Ferreira, Alessandra Couto de Camargo (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: Manual therapy has emerged as an option for facial rejuvenation treatment due to its effects on connective tissue. Objectives: The aim of the study was to verify the effectiveness of the manual therapy protocol in attenuating wrinkles and facial sagging. Methods: This is a quantitative-qualitative, randomized clinical trial. The study included female volunteers, aged between 40 and 50 years, distributed in 2 groups: Manual therapy group (MTG) and Control group (CG). The protocol used consisted of: lymph node decongestion, sliding massages, fast and vigorous movements, and traction on the fasciae. The evaluation instrument was through photos, in which they were analyzed by Dermato-functional specialists through a scale that graduates the wrinkles. The Shapiro-Wilk normality test was used to analyze the symmetry of the results by the Gauss curve. Pre- and post-intervention differences between the groups were determined using the non-parametric Wilcoxon test. Results: The average score obtained in the graduation of wrinkles and signs of aging in the manual therapy group showed significant differences in all regions of the face before and after treatment. And there was a decrease in the score, which shows improvement in the reduction of wrinkles and signs of aging, especially in the upper third. In contrast, in the control group, the average remained before and after the follow-up by the research, showing that there were no significant changes in this group. Conclusion: The manual therapy protocol showed significant results in reducing the signs of aging, such as fine lines and wrinkles, being another option to be applied in clinics.